Poland : The Social Safety Net During the Transition - Maret, Xavier (IMF Working Papers; Working Paper, 1993)
This paper argues that the brunt of the reform-induced increase in Polish social expenditures has been borne by social insurance arrangements (mainly pensions and unemployment compensation) rather than by social assistance schemes targeted to the poor or more temporary social safety net schemes. This is largely due to ease of access to social security and its more attractive benefit structure. Much of recent social expenditure reform had an ad-hoc nature and was driven by the need to alleviate looming financial distress. A major policy challenge is to avoid a further burdening of social security by needs that should be addressed by basic income support and emergency assistance policies or by general transfers (e.g., family allowances). Current reform needs are illustrated by using unemployment benefits and pensions as examples.